2015
DOI: 10.1098/rspa.2014.0703
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the growth rate of stress corrosion cracks

Abstract: This paper is a synthesis of earlier results supplemented by new results to define a comprehensive analysis of the growth rate of stress corrosion cracking (SCC). Two mechanisms, anodic dissolution (AD) and hydrogen embrittlement (HE), have been considered to calculate the SCC growth rate of AA 7050-T6 for a surface-breaking crack with blunt tip in an aqueous environment. The relative contributions of each mechanism and their mutual interactions have been quantitatively assessed. Results show that AD provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Classical plasticity equates this distance to the location of maximum stress [13][14][15][16][17][18][19][20][21][22][23], evident in Figures 1 and 4. This classical xcrit is 6 to 13 μm for K500 at KI of 25 to 45 MPam and 5 to 10 μm for AM100 at KI of 30 to 50 MPa√m.…”
Section: Fracture Process Zone Definitionmentioning
confidence: 99%
“…Classical plasticity equates this distance to the location of maximum stress [13][14][15][16][17][18][19][20][21][22][23], evident in Figures 1 and 4. This classical xcrit is 6 to 13 μm for K500 at KI of 25 to 45 MPam and 5 to 10 μm for AM100 at KI of 30 to 50 MPa√m.…”
Section: Fracture Process Zone Definitionmentioning
confidence: 99%
“…Two recent developments have arguably brought a stepchange to the modelling of environmentally assisted fracture. First, larger computer resources and new algorithms enable simulating coupled physical processes such as the transport of various dilute species (chemistry), the distribution of the electric field and current density (electrochemistry) and the deformation of materials (mechanics), so-called multi-physics modelling [3,4]. It is now possible to simulate the concurrent physical processes occurring not only within the material but also in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [ 30 ] found that the corrosion rate of Alloy 690 in a primary water environment reached its maximum at 250 °C. In addition, Lee [ 31 ] developed a comprehensive SCC growth rate model and De Meo [ 32 ] reported a numerical multiphysics peridynamic framework for the modeling of adsorbed-SCC based on the adsorption induced decohesion mechanism.…”
Section: Introductionmentioning
confidence: 99%